(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Epistaxis is a common otolaryngological emergency worldwide affecting up to 60% of the population in their lifetime. This study was conducted to describe the etiological profile and treatment outcome of epistaxis at Dhaka Medical College Hospital, a tertiary care hospital in BANGLADESH. Objective: The study is carried out with an objective to evaluate on etiological profile and management of epistaxis. Methods: This cross sectional study was conducted among the emergency and admitted patient with epistaxis at Dhaka Medical College Hospital from 1st November 2013 to 30th April 2014. Results: During the period under study, a total 104 patients were studied. The etiology of the cause of epistaxis was grouped into traumatic and non- traumatic. Among them 46 (44.23%) patient were in traumatic epistaxis and 58 (55.77%) patient were in non traumatic epistaxis. Male were affected more frequently than female in this study. There were 74 (71.15%) male and 30 (28.85%) females with a male female ratio of 2.47:1 Majority of the patients in this study were in 2nd decade (21.15%) followed by 6th decade (19.23%) and 3rd decade (17.31%). Among the 104 patients with epistaxis 78 (75%) were urban habitat and 26 (25%) were rural habitat. Significantly more patients were from urban resident. Regarding etiology and sex distribution there were no significant differences between urban and rural habitat. The present study shows that the most common cause of epistaxis was trauma (44.23%) followed by idiopathic (25%) and hypertension (17.31%). Local pain (41.31%), nasal obstruction (13.04%), nasal deformity (17.39%) associated other injury (13.04%) was more frequent in traumatic patient. Significant raise of blood pressure (Systoloic BP >160 mm Hg and diastolic BP > 100 mm Hg) were found in 58 (55.77%) non-traumatic patient. Severity of the nasal bleeding was mild to severe degree in both the groups. Significantly anterior epistaxis is common among the traumatic epistaxis group (69.57%) and posterior epistaxis in non-traumatic epistaxis group (46.55%). About 27.59% patient the exact site was not detected as there was diffuse bleeding. In case of nasal bleeding, bleeding from septum 42 (40.38%), from lateral wall 32 (30.76%) and from floor of the nose 23 (22.15%). Control of bleeding by the direct method was possible in 11 (10.57%) patients. Anterior nasal packing was given in 86 (82.69%) patients and post nasal packing was given in 3 (2.89%) patients. Conclusion: A high incidence in young adults was reported with preponderance of males over females. Occurrence of different types of epistaxis was strongly related with the certain demographic factors like age, sex and habitat of the patient. This study supports the credibility of conservative management procedure in the treatment of epistaxis. Simple nasal packing is the commonly practice conservative method with high success. Hence, this approach should be the preferred option in the management of epistaxis especially in developing countries. Bangladesh J Otorhinolaryngol; April 2020; 26(1): 45-54